Brief Report: Spuriously Low Serum IgG4 Concentrations Caused by the Prozone Phenomenon in Patients With IgG4‐Related Disease. Issue 1 (January 2014) - Khosroshahi, Arezou; Cheryk, Lynn A.; Carruthers, Mollie N.; Edwards, Judith A.; Bloch, Donald B.; Stone, John H.
<x xml:space="preserve">Abstract</x> Objective To determine the frequency of the prozone effect in patients with IgG4‐related disease (IgG4‐RD). Methods After identifying the prozone effect in an index patient with IgG4‐RD, we examined additional samples to determine the frequency of this phenomenon. Thirty‐eight serum samples obtained from patients with IgG4‐RD whose results had been reported previously were retested. The serum IgG4 concentrations determined by this repeat analysis were compared with the originally reported values. Results In 10 (26%) of 38 patients, the originally reported IgG4 values were falsely low; the prozone effect was identified in each of these 10 samples. Correction of the prozone effect by sample dilution led to revision of the mean serum IgG4 concentration in the 10 samples, from 26 mg/dl to 2, 008 mg/dl (normal range 2.4–121 mg/dl). All 10 patients whose samples were affected by the prozone effect had active IgG4‐RD. Failure to detect the elevated serum IgG4 concentrations had a direct impact on the decision not to institute treatment in these patients. Conclusion The prozone effect may lead to major underestimations of IgG4 concentrations in patients with IgG4‐RD and offers a potential explanation for the poor correlation observed between disease activity and serum IgG4 levels in some patients. This phenomenon should be considered if the serum IgG4 measurement appears discordant with the clinicopathologic diagnosis and the clinical assessment of disease activity.